Legacies of violence : history, society, and the state in Sardinia - Sorge, Antonio, 1975- (Anthropological horizons., 2015)
In Legacies of Violence, Antonio Sorge examines highland Sardinia's long history of resistance to outside authority and the effects that a history of violence exercises on collective representations.